Integrating social dynamics in the participatory modeling of small-scale cattle farmers’ perceptions and responses to climate variability in the Yucatan Peninsula, Mexico - Pérez-Lombardini, Fernanda; Siqueiros-García, Jesús M.; Solorio-Sánchez, Francisco Javier; Galindo, Francisco (Frontiers in Sustainable Food Systems, 2024)
Climate variability poses multifaceted challenges for livestock production. Rising temperatures and shifting rainfall patterns impact crop and pasture yields, reduce water availability, and contribute to livestock diseases, particularly affecting small-scale cattle producers dependent on climate-sensitive resources. Sustainable livestock farming promotes integrating best practices to enhance productivity while responsibly managing natural resources, but often overlooks relevant social dynamics. Social factors are excluded when promoting and studying the adoption of practices for sustainable cattle farming. This study aims to understand the factors and interactions between the social, animal and ecological systems within the small-scale cattle socioecosystems in the southern region of the Yucatan Peninsula, exploring cattle farmers’ perspectives on climate change, as well as their strategies and responses to extreme events like drought. Using fuzzy cognitive maps and scenario development as participatory and reflection methodologies, we found a conceptual gap between climate change and drought, indicating a lack of sustainable adaptive thinking toward these challenges. Interestingly, we found that local social organization, cultural dynamics, and spiritual practices are equally significant factors than technical and environment-oriented changes to the management of ranches in shaping an optimal cattle farming scenario. Our findings reveal that the management of cattle farms involves complex interplay among technical, environmental, social, political, and cultural elements, highlighting the inherent need to consider social values and preferences as fundamental components of sustainability. This study establishes the initial groundwork for employing participatory modeling with social actors engaged in the small-scale cattle context in Yucatan. The goal is to emphasize the importance of the social dimension in the general management of the small-scale cattle socioecosystem, thus in promoting sustainable cattle farming.